Design and optimization of four-terminal mechanically stacked and optically coupled silicon/perovskite tandem solar cells with over 28% efficiency - Ehsan, Raza (2023)
Silicon/perovskite tandem devices are believed to be a favorite contender for improving cell performance over the theoretical maximum value of single-junction photovoltaic (PV) cells. The present study evaluates the design and optimization of four-terminal (4-T) mechanically stacked and optically coupled configurations using SCAPS (solar cell capacitance simulator). Low-cost, stable, and easily processed semitransparent carbon electrode-based perovskite solar cells (c-PSCs) without hole transport material (HTM) and highly efficient crystalline silicon (c-Si) PV cells were utilized as top and bottom cells, respectively. The wide bandgap multi-cation perovskite Csx(FA0.4MA0.6)1−xPbI2.8Br0.2 and a low bandgap c-Si were employed as light-harvesting layers in the top and bottom cells, respectively. The impact of perovskite thickness and doping concentrations were examined and optimized for both tandem configurations. Under optimized conditions, thicknesses of 1000 nm and 1100 nm are the best values of the perovskite absorber layer for 4-T mechanically stacked and optically coupled arrangements, respectively. Likewise, 1 × 1017 cm−3 doping concentration of top cells revealed the highest performance in both structures. With these optimized parameters under tandem configurations, efficiency values of 28.38% and 29.34% were obtained in 4-T mechanically and optically coupled tandems, respectively. Results suggest that by optimizing perovskite thickness and doping concentration, the proposed designs using HTM-free c-PSCs could enhance device performance.